2016
DOI: 10.1007/s40271-016-0213-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Benefits and Factors that Influence the Ability to Establish and Maintain Patient Support Groups in Rare Diseases: A Scoping Review

Abstract: Rare disease support groups are an important source of emotional and practical support for many patients. There is no trial evidence on the benefits of these groups and limited evidence on the perceived benefits and barriers and facilitators to establishing and maintaining them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 32 publications
2
58
0
1
Order By: Relevance
“…Social support was the most beneficial coping strategy reported in this study. Social support has been shown to help maintain well‐being and act as a buffer against distress and depression . In the current study, some of the participants knew others with the condition, or attended a support group, and really valued the understanding and support of people they felt understood their pain.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Social support was the most beneficial coping strategy reported in this study. Social support has been shown to help maintain well‐being and act as a buffer against distress and depression . In the current study, some of the participants knew others with the condition, or attended a support group, and really valued the understanding and support of people they felt understood their pain.…”
Section: Discussionmentioning
confidence: 80%
“…Social support has been shown to help maintain well-being and act as a buffer against distress and depression. 25,26 In the current study, some of the participants knew others with the condition, or attended a support group, and really valued the understanding and support of people they felt understood their pain. Peer support appeared to decrease feelings of shame for participants by normalizing the condition for them.…”
Section: Discussionmentioning
confidence: 89%
“…13 Patients and patient organizations play a critical role in rare disease European Reference Networks due to their expertise. 13,[41][42][43] Patients and/or their representatives become increasingly involved in addressing ethical issues, transparency in quality of care, safety standards, and contributing to research. 13,44,45 The involvement of representatives of patient support groups in this consensus conference allowed a unique perspective to all discussed aspects of patient care and management and emphasizes the benefits of collaboration as already proved in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Access to support groups in SSc can potentially be improved by offering them in a virtual format. Indeed, a scoping review of facilitators and barriers for support groups across rare diseases found that holding support groups via teleconference was an important facilitator [18]. A recent systematic review of 17 studies of support groups for chronic health conditions concluded that using videoconferencing to deliver support groups is feasible and may improve the accessibility of support group interventions [19].…”
Section: Discussionmentioning
confidence: 99%